Assessment of Maltreatment in Forensic Traumatology Through a Case Report - Erkman, Fatma Tuğba; Tümer, Ali Rıza; Akçan, Ramazan (The Bulletin of Legal Medicine, 2022)
Maltreatmen has been defined and prohibited as inhuman or mistreatment incompatible with human dignity. A 20-year-old male-patient presented to us with allegation of being victim of ill-treatment. In the anamnesis he stated that he was captured in a house, had been subjected to violence, beaten, burned with hot objects, threatened. In his examination, it was determined that he had widespread ecchymoses, abrasions and burns of different origin all over his body. At first and/or forensic medical examination of a person exposed to trauma, it cannot be expected to know the legal meaning of the act to which they have been subjected. In order not to cause the victim’s legal-loss, he should know the legal equivalent of the ill-treatment and evaluate the patient in this respect. In this study, the issues to be taken into consideration by forensic medicine specialists who encounter trauma and medicolegal information to help diagnosis are discussed.